2002
DOI: 10.1093/embo-reports/kvf175
|View full text |Cite
|
Sign up to set email alerts
|

Targeted disruption of hsp70.1 sensitizes to osmotic stress

Abstract: The 70 kDa heat shock protein (Hsp70) plays a critical role in cell survival and thermotolerance in response to various stress stimuli. Two nearly identical genes, hsp70.1 and hsp70.3, in response to environmental stress, rapidly induce Hsp70. However, it remains unclear whether these two genes are differentially regulated by various stresses. To address the physiological role of the hsp70.1 and hsp70.3 genes in the stress response, we generated mice that specifically lack hsp70.1. In contrast to heat shock, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
71
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 19 publications
4
71
0
Order By: Relevance
“…The coordinated induction of these genes is crucial for cell survival (4,46). Because the kidney is the only organ where extreme hyperosmolality is regularly encountered because of the operation of the urine concentration mechanism, it is conceivable that prompt nuclear accumulation of OREBP/TonEBP, as mediated by NLS, is a key step in the timely induction of gene expression to ensure cellular protection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The coordinated induction of these genes is crucial for cell survival (4,46). Because the kidney is the only organ where extreme hyperosmolality is regularly encountered because of the operation of the urine concentration mechanism, it is conceivable that prompt nuclear accumulation of OREBP/TonEBP, as mediated by NLS, is a key step in the timely induction of gene expression to ensure cellular protection.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertonicity also induces the expression of heat shock protein 70 (HSP-70) (3) that acts as a molecular chaperone to protect cells from osmotic stress-induced apoptosis (4). The accumulation of organic osmolytes is brought about by the induction of a battery of genes, including aldose reductase (AR), betaine/␥-aminobutyric acid transporter (BGT-1), and Na ϩ -dependent myoinositol transporter (SMIT), which is responsible for the synthesis of sorbitol and the uptake of betaine and myoinositol, respectively.…”
mentioning
confidence: 99%
“…It has been previously shown that hsp70.1 is responsible for inducing Hsp70 in response to hypertonic stress in mice, and plays a cytoprotective role against the stress Shim et al, 2002). Woo et al reported that the transcriptional activator Tonicity-responsive enhancer (TonE) binding protein (TonEBP) regulates the induction of hsp70.1 in response to hypertonic stress (Woo et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have suggested the possibility that hypertonic stress and hsp70 induction may be related to the human kidney disease process (Sheikh-Hamad et al, 2001;Shim et al, 2002;Dmitrieva and Burg, 2005). However, the induction of hsp70 by hypertonic stress as well as its protective role in human cell is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…No induction is observed after oxidative stress. [10][11][12] hsp70.1 is constitutively transcribed from one-cell stage to blastocyst stage, 13 whereas hsp70.3 is constitutively expressed from two-cell stage. 14 By the blastocyst stage, the expression of the two genes becomes heat inducible.…”
Section: Introductionmentioning
confidence: 99%